What is the carbon footprint of academic clinical trials? A study of hotspots in 10 trials - Peter Doran; Kerenza Hood; Rustam Al-Shahi Salman; Emma Bedson; Carrol Gamble; Paula R Williamson; Katie Gillies; Sarah Pett; Christine Newman; Xiaoying Chen; Craig Anderson; Naomi McGregor; et al. (BMJ Open, 2024)
Background Clinical trials are fundamental to healthcare, however, they also contribute to anthropogenic climate change. Following previous work to develop and test a method and guidance to calculate the carbon footprint of clinical trials, we have now applied the guidance to 10 further UK and international, academically sponsored clinical trials to continue the identification of hotspots and opportunities for lower carbon trial design.Methods 10 collaborating clinical trial units (CTUs) self-identified and a trial was selected from their portfolio to represent a variety of designs, health areas and interventions. Trial activity data was collated by trial teams across 10 modules spanning trial setup through to closure, then multiplied by emission factors provided in the guidance to calculate the carbon footprint. Feedback was collected from trial teams on the process, experience and ease of use of the guidance.Results We footprinted 10 trials: 6 investigational medicinal product trials, 1 nutritional, 1 surgical, 1 health surveillance and one complex intervention trial. Six of these were completed and four ongoing (two in follow-up and two recruiting). The carbon footprint of the 10 trials ranged from 16 to 765 tonnes CO2e. Common hotspots were identified as CTU emissions, trial-specific patient assessments and trial team meetings and travel. Hotspots for specific trial designs were also identified. The time taken to collate activity data and complete carbon calculations ranged from 5 to 60 hours. The draft guidance was updated to include new activities identified from the 10 trials and in response to user feedback.Discussion There are opportunities to reduce the impact of trials across all modules, particularly trial-specific meetings and travel, patient assessments and laboratory practice. A trial’s carbon footprint should be considered at the design stage, but work is required to make this common place.